A non-thermal modification method to enhance the encapsulation efficiency, stability, and slow-release performance of zein-based delivery systems – Cold plasma. (May 2023) - Zhou, Junjun; Bian, Yaqing; Yang, Tongliang; Wang, Jiake; Kong, Tianai; Zhang, Yifu; Chen, Ye; Li, Shuhong
Abstract: Zein is widely used as a nutrient/drug delivery carrier due to its self-assembling property. However, the low encapsulation efficiency (EE) and stability limit its applications. In this study, zein nanoparticles are modified by cold plasma technology. The characterization results show that the modified zein exhibits more uniformly dispersed spheres with a more ordered secondary structure (increased α-helix, β-turn, and reduced β-sheet), but the molecular weight is not affected. The modified nanoparticles (85 W, 2 min) have a smaller particle size (100.03 nm) and a larger ζ-potential (41.07 mV). When used as delivery wall material, their stronger self-assembling dynamics and more binding sites enhance the interactions between zein and curcumin. This causes an enhancement in the curcumin burst release property, EE (52.83%–76.31%), pH, ionic strength, and storage stability. Therefore, cold plasma is an effective modification method to improve the EE, stability, and slow-release properties of zein-based delivery systems. Highlights: Cold plasma (CP) affects the structures and properties of zein. Delivery effect is related to changes in protein properties and structures. CP enhances the stability and interaction of nanoparticle delivery system. Encapsulation efficiency and slow-release are improved by CP.